Single Atoms on Graphene for Energy Storage and Conversion. Issue 9 (16th April 2019) - Zhang, Linlin; Wang, Yijing; Niu, Zhiqiang; Chen, Jun
Abstract: Single atoms are attracting much attention in the field of energy conversion and storage due to their maximal atomic utilization, high efficiency, and good selectivity. Moreover, their unique electronic structure could improve the intrinsic activity of the active sites. However, the high surface free energy of single atoms inevitably results in their serious aggregation, leading to degraded catalytic activity and poor cycling life. To solve these issues, supports with high surface areas have to be developed to reduce loading density of single atoms and further decrease the surface free energy. Furthermore, engineering the active sites of these substrates can also regulate chemical coordination of single atoms, enhancing their catalytic performance. Owing to high surface area, excellent conductivity and adjustable surface properties, graphene is widely utilized to load atomic metal catalysts. In this review, the fabrication strategies and characterization methods of single atoms on graphene (SAG) are summarized first. Subsequently, the electrochemical applications of SAG on the oxygen reduction reaction, oxygen evolution reaction, hydrogen evolution reaction, carbon dioxide reduction, and methane oxidation are discussed in detail. Finally, the future developments and prospects in fabrication and application of SAG are also discussed. Abstract : In this review, the fabrication strategies and characterization methods of single atoms on graphene (SAG) are summarized. In addition, the electrochemical applications of SAG on the oxygen reduction reaction, oxygen evolution reaction, hydrogen evolution reaction, carbon dioxide reduction, and methane oxidation are also discussed. Finally, the future developments and prospects in fabrication and application of SAG are also discussed.